Perceptions of adopters versus non-adopters of a patient portal: an application of diffusion of innovation theory. Issue 3 (1st July 2018) - Emani, Srinivas; Peters, Ellen; Desai, Sonali; Karson, Andrew S.; Lipsitz, Stuart R.; LaRocca, Rajani; Stone, John; Suric, Vlad; Wald, Jonathan S.; Wheeler, Amy; Williams, Deborah H.; Bates, David W.
Abstract : Background: Patient portals have emerged as an important tool through which patients can access online health information and engage in their health care. However, we know little about how patients perceive portals and whether patient perceptions might influence portal adoption. Objective: Apply the diffusion of innovation (DOI) theory to assess perceptions of adopters and non-adopters of a patient portal. Methods: We conducted a cross-sectional survey of adopters and non-adopters of the portal. Our survey consisted of perceived attributes from the DOI theory, socio-demographic characteristics and patient perceptions of technology adoption. Results: Three factors representing perceived attributes from DOI theory accounted for 73% of the variance in the data: Factor 1 – Relative Advantage (27%); Factor 2 – Ease of Use (24%) and Factor 3 – Trialability (22%). Adopters perceived greater Relative Advantage [mean (SD)] = 3.8 (0.71) versus 3.2 (0.89), p < 0.001, Ease of Use = 4.1 (0.71) versus 3.3 (0.95), p < 0.001 and Trialability = 4.0 (0.57) versus 3.4 (0.99), p < 0.001 than non-adopters. In multivariate modelling, age [OR = 3.75, 95% CI: (2.17, 6.46), p < 0.001] and income [OR = 1.87, 95% CI: (1.17, 3.00), p < 0.01] predicted adoption of the portal. Among DOI factors, Relative advantage predicted adoption of the portal [OR = 1.48, 95% CI: (1.03, 2.11), p < 0.05]. Conclusion: Patients will adopt a patient portal if they perceive it to offer a relative advantage over existing practices such as telephoning or visiting the doctor's office. Organisations seeking to increase the adoption of patient portals should implement strategies to promote the relative advantage of portals as, for example, through posters in waiting and exam rooms. A digital divide in the adoption of patient portals may exist with respect to age and income.